PERTIMBANGAN HAKIM DALAM PENETAPAN PERMOHONAN DISPENSASI KAWIN SEBAGAI UPAYA MENUTUP MALU AKIBAT HAMIL DI LUAR NIKAH (Studi Putusan Pengadilan Agama Kelas 1B Sengkang Nomor 1/Pdt.P/2020/PA.Skg. Perspektif Hukum Islam) - Iffah Annisa Faulia Gusti Hasan; Hartini Tahir; Musyfikah Ilyas (Universitas Islam Negeri Alauddin Makassar, 2022)
This research discusses how the Judge's Consideration of the Application for Marriage Dispensation as an Effort to Cover Shame due to Pregnancy Out of Wedlock (Study of the Decision of the Sengkang Class 1B Religious Court Number 1/Pdt.P/2020/PA.Skg Perspective of Islamic Law)